Transport Stress Induced Cardiac NO-NOS Disorder Is Mitigated by Activating Nrf2/HO-1/NQO1 Antioxidant Defense Response in Newly Hatched Chicks - Xu, Hao-Liang; Li, Hui; Bao, Rong-Kun; Tang, Yi-Xi; Elsherbeni, Ahmed Ibrahim Ahmed; Gharib, Hassan Bayoumi Ali; Li, Jin-Long (Frontiers in Veterinary Science, 2022)
With the development of the intensive poultry industry, the health problems of chickens caused by transportation have attracted more and more attention. Transport stress reduces performance, immune function, and meat quality in chicks, which has become one of the most important factors that endanger the development of the poultry industry. Currently, studies on the effects of transport stress have mainly focused on the performance of livestock and poultry to be slaughtered. However, the effects of transport stress on heart damage and oxidative stress in newborn chicks have not been reported. In this study, we selected newborn chicks as the object. This study was intended to explore the effects of transport stress on the heart damage of newly hatched chicks. The findings suggested that transport stress could cause oxidative stress in the hearts of newly hatched chicks by increasing the levels of malondialdehyde (MDA), hydrogen peroxide (H2O2) and decreasing the contents of Total antioxidant capacity (T-AOC), and the activities of antioxidant enzymes (SOD), together with increasing the activities of antioxidant enzymes (Catalase (CAT) and Glutathione S-transferase (GST)). Transport stress disrupted the balance between oxidation and antioxidant systems. The Nrf2 signaling pathway was activated by transport stress and triggered the transcription of antioxidant signaling. In short, transport stress-induced nitric oxide (NO)—nitric oxide synthases (NOS) system metabolic disorders and cardiac oxidative stress are mitigated by activating the nuclear factor-erythroid 2-related factor 2 (Nrf2)/heme oxygenase-1 (HO-1)/NAD(P)H quinone oxidoreductase-1 (NQO1) antioxidant defense response in newly hatched chicks.